Assessment of obstructive sleep apnea rate and associated factors among Lebanese adults: a cross-sectional study - Kaddoura, Tala; Hodroj, Mohamad; Chmeis, Bilal; Rammal, Fatima; Malhab, Sandrella Bou; Mansour, Sara; Akour, Amal; El Khatib, Sami; Hosseini, Basile; Hallit, Souheil; Malaeb, Diana; Hosseini, Hassan (Frontiers in Public Health, 2025)
ObjectivesTo estimate the rate of obstructive sleep apnea (OSA) and associated factors among Lebanese adults.MethodsA cross-sectional study was conducted in February–April 2022; 1,202 Lebanese adults were enrolled. The sample was collected among several Lebanese governorates through an anonymous online self-reported questionnaire. The STOP-BANG questionnaire was used as a screening tool to estimate the OSA risk. “Low OSA risk” is established with 0–2 positive answers, “Intermediate OSA risk” is established by 3–4 positive answers while “High OSA risk” is established by 5–8 positive answers.ResultsThis study showed that 743 (62.4%) of the sample had low risk for OSA, 357 (30.0%) had moderate, and 90 (7.6%) had high risk for OSA. Older age (aOR = 1.05) and having hypertension (aOR = 7.80) were associated with higher odds of moderate OSA. Female sex (aOR = 0.04) was significantly associated with lower odds of moderate OSA compared to males. Older age (OR = 1.17), higher BMI (OR = 1.14), hypertension (OR = 18.55), and having severe COVID-19 infection compared to mild (OR = 4.30) were significantly associated with higher odds of high OSA, whereas female sex (OR = 0.002) and being married compared to single (aOR = 0.23) were associated with lower odds of high OSA.ConclusionThis study showed that most Lebanese adults have low risk for OSA. It also confirmed that sex, age, obesity, hypertension, and severe COVID-19 were associated with high OSA risk. These associated factors call for future research exploring the causes including the potential effect of social, economic, and political instability, local customs, and environmental factors. Moreover, future health campaigns should be assigned to increase awareness among Lebanese population regarding the prevention of OSA through lifestyle modifications.